Encephalitis associated with inappropriate antidiuretic hormone secretion due to chikungunya infection in Recife, State of Pernambuco, Brazil - Lucena-Silva, Norma (2017)
Fundação Oswaldo Cruz. Centro de Pesquisa Aggeu Magalhães. Departamento de Imunologia. Recife, PE, Brasil.